Методи виявлення та розпізнавання БПЛА - Каспар’янц, А. В.; Щічко, О. О.; Печенов, М. А. (ХНУРЕ, 2023)
Methods of detection and recognition of unmanned aerial vehicles in acoustic, optical, radar systems are considered. The advantages and disadvantages of the main varieties of methods are analyzed. It is shown that for different systems there is a method of UAV detection
Keywords: розпізнавання БПЛА